PENGARUH PROFITABILITAS DAN LABA BERSIH TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Panggabean, Nazlah Rachma; Andani, Merry; Silitonga, Renita (JURNAL NERACA AGUNG, 2020)
This study aims at determining the extent of the influence of profitability (X1) and net income (X2) on stock prices (Y). Secondary data used in this study is in the form of financial reports of companies manufacturing food and beverage sectors listed on the Indonesian Stock Exchange (Bursa Efek Indonesia). The independent variable in this study is profitability and net income, while the dependent variable is the stock price. The analytical method used is multiple linear regression, F test (simultaneous test) and t test (partial test). The multiple linear regression equation is done through SPSS version 20Y = 309,930 + 0.93 X1 + 1,386X2. T test results of the t-variable profitability (0.322) <t table (2.048) with a significant value of 0.04, it can be concluded that the profitability variable (X1) has a positive effect on the variable price of shares (Y). While the results of the study of net income variables that count (2,025) < table (2,048) with a significant level above 0.031, then it can be concluded that the variable net income (X2) has a significant effect on the variable price of shares (Y). The results of the partial F hypothesis test are F of 2.597 and significant significance is 0.093. Because the significance is significantly lower than 0.05 (α = 0.05), the hypothesis is accepted. The results show the relationship between profitability to positive stock prices and the coefficient of determination (R square ) of = 0.161. This means that the share price is influenced by 16.6% by profitability.